An approach for evaluating residual capacity of reinforced concrete beams exposed to fire. (1st March 2016) - Kodur, V.K.R.; Agrawal, Ankit
Highlights: An approach is proposed for evaluating post-fire residual capacity of concrete beams. Response of concrete beams under ambient, fire, and post-fire conditions is traced. Distinct properties in heating and cooling phases are considered in evaluating response. Applicability of the residual capacity approach is illustrated through a case study. Abstract: This paper presents an approach for assessing the residual capacity of fire exposed reinforced concrete (RC) beams. The approach involves capturing response of RC beams in three stages, namely, structural response at ambient conditions, thermo-mechanical response during fire exposure, and post-fire residual response after cooling down of beams. Distinct material properties of reinforcing steel and concrete are considered during heating and cooling phase of fire exposure and residual (after cool down) phase of analysis. In addition, relevant load level, specific fire scenarios, boundary conditions, and plastic deformations that develop in a beam during fire exposure are also incorporated in evaluating residual response of fire exposed RC beams. The proposed approach is implemented using a detailed numerical model developed in the finite element computer program ABAQUS. Predictions from the numerical model show good correlation with the response parameters measured in experiments for evaluating residual capacity of fire exposed RC beams. Also, predictions of residual capacity from the finite element analysis are compared with that obtained from simplified sectional analysis based on maximum rebar temperatures consideration. This comparison indicates that the finite element analysis yields more realistic predictions of residual capacity than that predicted from simplified sectional analysis. The applicability of the proposed approach in evaluating residual capacity of fire exposed RC beams is illustrated through a case study.